Prevalence of Suicidal Ideation in Patients With COVID-19 Admitted to a Hospital in Qazvin, Iran - Masoumeh Saberi; Samira Dodangeh; Seyed Jafar Adnani Sadati; Zahar Sadat Mohammadi; Seyedeh Zahra Hashemi5 (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum)
Background and Objectives: Many patients with COVID-19 show long-term physical and mental symptoms. This study aims to determine the prevalence of suicidal ideation in patients with COVID-19 hospitalized in a hospital in Qazvin, Iran. Methods: This is a cross-sectional study. The study population consists of all patients with COVID-19 admitted to Bou Ali Sina Hospital in Qazvin city. A two-part questionnaire was used to collect data; the first part surveys demographic characteristics, history of death due to COVID-19 in relatives, history of underlying disease, days of hospitalization, history of intubation, and history of hospitalization in intensive care units. The second part was the Beck Scale for Suicide Ideation. The collected data were analyzed in SPSS software, version 23 using ANOVA and logistic regression analysis. Results: Participants were 206 patients with COVID-19. The data showed that 12.8% of patients had high suicidal ideation. Younger patients were at a high risk of suicide (Mean age: 31.96±12.59 years) (P<0.001). In addition, patients who were single (P<0.001) and had a history of death due to COVID-19 in relatives or friends had higher suicidal ideation (P=0.005). Conclusion: About 12.8% of patients with Covid-19 admitted to the study hospital had a high suicidal ideation. There is no considerable difference between the prevalence of suicidal ideation reported in this study and the data reported for the general population of Iran before the pandemic.